2019
DOI: 10.1371/journal.pone.0212207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stability and stepping strategies of young healthy adults walking on an oscillating treadmill

Abstract: Understanding how people modify their stepping to maintain gait stability may provide information on fall risk and help to understand strategies used to reduce loss of balance. The purpose of this study was to identify the stepping strategies healthy young individuals select to maintain balance while walking on a destabilizing surface in various directions. A treadmill mounted on top of a 6 degree-of-freedom motion base was used to generate support surface oscillations in different degrees of freedom and ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
7
20
0
Order By: Relevance
“…Consistent with the aforementioned paradox (Li and Huang, 2021;McAndrew Young et al, 2012;Onushko et al, 2019), all participants here demonstrated larger average MoSML when subjected to mediolaterally destabilizing perturbations (Fig. 4A).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with the aforementioned paradox (Li and Huang, 2021;McAndrew Young et al, 2012;Onushko et al, 2019), all participants here demonstrated larger average MoSML when subjected to mediolaterally destabilizing perturbations (Fig. 4A).…”
Section: Discussionsupporting
confidence: 83%
“…Given the fundamental ideas underlying MoSML, these larger values suggest greater mediolateral stability, despite clearly destabilizing intrinsic and/or extrinsic factors. Some studies assume such counterintuitive results reflect a compensatory strategy used to reduce likelihood of balance loss (Madehkhaksar et al, 2018;Onushko et al, 2019). This cannot explain why balanceimpaired and extrinsically-destabilized individuals remain at elevated risk for sideways falls.…”
Section: Discussionmentioning
confidence: 99%
“…In another study that applied lateral shift perturbations at early single leg support, people used the gluteus medius of their swing leg to place their subsequent foot more outward (Afschrift et al 2018) in the direction of the potential fall (Reimann et al 2018; Wang and Srinivasan 2014), which would help increase the MoS to maintain a more stable body position (Hof et al 2005). Larger MoS often occurs in response to medial-lateral treadmill shift perturbations (Hak et al 2012; McAndrew Young et al 2012; Onushko et al 2019), similar to the increased MoS ML in our L1 perturbation. Interestingly, subjects maintained this increased MoS ML for the Stick0.4 perturbation but gradually reduced the MoS ML for the L1 perturbation, suggesting that subjects either could not or did not have a reason to decrease MoS ML while gaining more experience with the Stick0.4 perturbation.…”
Section: Discussionsupporting
confidence: 73%
“…The copyright holder for this preprint this version posted March 1, 2021. ; https://doi.org/10.1101/2021.02.27.433210 doi: bioRxiv preprint McAndrew Young et al 2012;Onushko et al 2019), similar to the increased MoSML in our L1 perturbation. Interestingly, subjects maintained this increased MoSML for the Stick0.4 perturbation but gradually reduced the MoSML for the L1 perturbation, suggesting that subjects either could not or did not have a reason to decrease MoSML while gaining more experience with the Stick0.4 perturbation.…”
Section: Discussionsupporting
confidence: 66%
“…Assuming that the unilateral support phase on the faster moving side of the treadmill is shorter, and therefore the stability margin is greater, the cycle-averaged xCOM should shift away from the faster moving leg. On the other hand, humans and presumably cats can voluntarily increase or decrease margins of stability by, for example, walking with a wide or narrow step width to minimize the risk of falling in an unstable environment or to satisfy task demands [5,23,34,35]. However, both humans and cats prefer shifting COM towards a slower belt.…”
Section: Discussionmentioning
confidence: 99%